(untitled) (Archives of Mechanics - Test, 2006)
The reflection and refraction of thermoelastic plane waves at an imperfect interface between two dissimilar thermoelastic solid half-spaces has been investigated. The thermoelastic theory without energy dissipation developed by Green Naghdi [18] has been used to study the problem. The amplitude ratios of various reflected and refracted waves are obtained for an imperfect boundary. Particular cases of normal stiffness, transverse stiffness, slip and welded boundaries are discussed. The amplitude ratios are also deduced at the interface of two semi-infinite media (i) Elastic/Thermoelastic without energy dissipation, (ii) Thermal Conducting Liquid/Thermoelastic without energy dissipation, (iii) Non-viscous Fluid/Thermoelastic without energy dissipation, (iv) Thermal Conducting Liquid/Thermal Conducting Liquid and (v) Elastic/Elastic. It is found that the amplitude ratios of various reflected and refracted waves are affected by the stiffness and thermal properties of the media. The amplitude ratios of reflected waves are also deduced for a special case of stress-free boundary.